Health policy and its implementation in small island developing states in the British West Indies - Mc Naught, Alan (2003)
Seeks to determine to what extent policy theory and the tools of policy analysis could be used to explain the nature and outcomes of the health policy and implementation process. Presents case studies from Anguilla and the British Virgin Islands.